2017
DOI: 10.1183/13993003.00889-2017
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment, prognosis and guideline implementation in pulmonary arterial hypertension

Abstract: @ERSpublicationsSimplified risk assessment using the number of low-risk criteria predicts prognosis at baseline and follow-up in PAH http://ow.ly/KMsj30cPNbmCite this article as: Boucly A, Weatherald J, Savale L, et al. Risk assessment, prognosis and guideline implementation in pulmonary arterial hypertension. Eur Respir J 2017; 50: 1700889 [https://doi.org/ 10.1183/13993003.00889-2017.ABSTRACT Current European guidelines recommend periodic risk assessment for patients with pulmonary arterial hypertension (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
692
8
56

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 587 publications
(779 citation statements)
references
References 22 publications
23
692
8
56
Order By: Relevance
“…A study from the French registry demonstrated clearly that in order to achieve a better long-term prognosis, patients need to have as many parameters as possible in the low-risk category. In this study, PAH patients who achieved only one or two low-risk criteria during the first year of PAH treatment had worse outcomes than those who achieved three or four low-risk criteria [18].…”
Section: Role Of Risk Assessment In Pahmentioning
confidence: 85%
“…A study from the French registry demonstrated clearly that in order to achieve a better long-term prognosis, patients need to have as many parameters as possible in the low-risk category. In this study, PAH patients who achieved only one or two low-risk criteria during the first year of PAH treatment had worse outcomes than those who achieved three or four low-risk criteria [18].…”
Section: Role Of Risk Assessment In Pahmentioning
confidence: 85%
“…Since then, the age of IPAH patients has increased considerably, at least in Western countries [4,[8][9][10][11]. In Germany, the mean age of patients newly diagnosed with IPAH in 2014 was 65 years [12].…”
Section: Increasing Age and Mortality In Ipahmentioning
confidence: 99%
“…Recent studies from the French PH registry and from the European PH registry COMPERA have confirmed that IPAH patients who meet 3-4 distinct low risk criteria with targeted therapies have 5-year survival rates of 95% or higher [3,4]. Unfortunately, this was accomplished only in 19% of the patients in the French series and 9% of the patients in COMPERA [4,5]. The reasons why the majority of patients fail to reach a low risk profile with targeted therapies have not been fully explored.…”
mentioning
confidence: 99%
“…BOUCLY et al [15] concluded that the number of low-risk criteria present at diagnosis and at first re-evaluation (median 4.4 months) discriminated risk of death or lung transplantation.…”
mentioning
confidence: 99%
“…In the French registry (n=1017), BOUCLY et al [15] studied incident patients with idiopathic, heritable or drug-induced PAH. The number of low-risk criteria (FC I or II, 6MWD >440 m, mRAP <8 mmHg and CI ⩾2.5 L·min…”
mentioning
confidence: 99%